Double-layered wrap-around sensor network for three-dimensional positioning of acoustic emission sources and its effect on monitoring crack propagation in rock samples - Jing Yang; Zonglong Mu; Guangjian Liu; Shaokun Gong; Atif Javed; Jinglong Cao; Bofei Yang; Fang Yuan (International Journal of Distributed Sensor Networks)
The present sensor arrangement in a cubic way for monitoring crack propagation in rock samples exhibits shortfalls of blind monitoring zone and large deviation. This study proposes a double-layered wrap-around sensor network, which enhances the monitoring range and improves the location accuracy of acoustic emission source. Furthermore, based on the polar formation algorithm, acoustic emission source was positioned to explore the propagation of microscopic cracks in cylindrical rock samples and this was further validated by the acoustic emission activity index. The results show that: (1) The double-layered wrap-around sensor network exhibits considerably broader monitoring range and enhanced precision. The simulated fracture formed from cracks of high-energy release had a favorable consistency with the macro-failure surface of rock specimens; (2) During the loading process, acoustic emission activity had a significant positive correlation with signal amplitude and the number of events. In addition, acoustic emission activity of medium-grained sandstone showed a tendency of decreasing—remaining at a low value—increasing—remaining at a high value, which exactly corresponds to the four rock loading stages of compaction, elastic deformation, crack development, and crack connection; (3) rock samples experienced micro-cracking of low energy, micro-cracking of high energy, and crack connection in sequence in the failure process, which shows a high consistency between crack development and acoustic emission activity. Thus, acoustic emission activity could be used as an index for assessing the rock failure state.